Petrografia e geoquímica do granito Porto Grande, SE do Escudo das Guianas-AP - COELHO, Dayane do Nascimento (2019)
The southeastern portion of the Guayana Shield, on the eastern edge of the Amazonian Craton, was the object study of Serviço Geológico do Brasil - CPRM of Project Geologia da Folha Macapá, (BARBOSA ET AL 2013). During the geological mapping of Folha Macapá by Serviço Geológico do Brasil – CPRM, an important contribution was the definition of a granitic pluton, called the Granite Porto Grande, which was dated by Pb evaporation method in zircon at 1.84 Ga by Barbosa et al. (2013). The area selected for this work, which includes the Granite Porto Grande, is located in the northeast portion of the Folha Macapá, near the city of Porto Grande. The geochemical data, and petrographic gamaespectométricos produced in this study added data from the literature, allow some considerations that contribute to the understanding of magmatism Granite Porto Grande. The chemical data have shown that the rocks of the Granite Porto Grande are subalkaline of peraluminous nature, and have features that resemble granite Type-S, derived from sedimentary protolith or metasedimentary. The interpretation of gamaespectométricas images revealed high radiation in the Th and U channel and moderate in the K-bus, which is compatible with the nature of the rocks (granites). The petrographic data allowed the recognition of two lithofacies in Granite Porto Grande, the syenogranites biotite, with the highest expression in the body, and biotite monzogranites, both with significant ductile deformation suggesting that this body has syn-tectonic character, before that, it is possible to suggest that after 1.99 Ga, which is the lower limit accepted for the performance of the Trans Cycle, Amapá Block was affected by a tectonic-thermal event, evidenced by the placement of Granite Porto Grande, considering that ages around 1, 84 Ga are not known in the province